The importance of the history of comparative jurisprudence as the direction of scientific researches - Тюріна, Оксана Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
A short description of genesis of formation of comparative jurisprudence from the position of historical period and certain geographical forms is given in this article. Also some of potential possibilities of the history of comparative jurisprudence with the understanding of the law system are regarded in this article. Current stage of the comparative law shows a recognition of its status as a law science but this recognition has come a long and complicated way, researching of which gives an opportunity by detecting genesis not only to show the features of this scientific knowledge system and a special sphere of scientific research, but also to identify perspective ways of its development, improve methodological arsenal of the comparative law. Defined above causes the actuality of this article, an aim of which is to outline the potential opportunities of the direction of scientific researches as comparative law history for the comparative law itself as well as for the law science in general. The comparative law history as a direction of scientific researches can be considered: firstly, by meaningful aspect – as a summation of selected in some way regularities, tendencies, properties, relations and dependencies of comparative law; secondly, by the formal side – in the form of the results of the previous scientific law researches, theoretical constructions, conceptual apparatus etc. So, the meaning of the comparative law history as a direction of scientific researches is an opportunity to deepen the knowledge about nature and potential subject – methodological opportunities of the comparative law as well as the law system at its level as a national phenomenon and a theoretical and legal category.